BASIC PRINCIPLES OF USING VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN THE PROCESS OF TEACHER TRAINING IN UKRAINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In our opinion, in all aspects, education should correspond to the modern realities of the world, for life and communication with which we prepare a person. We propose to pay attention to the preparation of the individual, because without the readiness of the teacher to fulfil his or her responsibilities for socialization and development of skills necessary for self-realization, we lose not only a favourable period. We lose time and opportunities for a person's success in life.For example, teachers' lack of skills or knowledge of currently popular audio-visual content programs, building effective communication in social networks, and their quality use in the educational process create a  «generation gap». After all, «gaps» in the knowledge, skills, and capabilities of a teacher or professor are immediately «striking» to children and young people, causing them to reject the teacher's personality and, as a result, the information they broadcast.In addition, a modern young person, fascinated by the possibilities of gadgets and gamification in education, constantly needs new impressions, sensations that will allow them to engage in the educational process, and will interest young people who are oversaturated with various types of information. That is why, in this review, we outlined the main points of our use of currently available virtual and augmented reality technologies, in particular the AltspaceVR program, in the practice of training primary school teachers. We also presented our experience and various aspects of using these technologies in the Ukrainian educational space.